Regulating Inductive Reasoning In Sexual Assault Cases - Tanovich, David M. (2017)
Justice Marc Rosenberg will be remembered as one of Canada’s greatest criminal law jurists by those fortunate enough to have worked with him, to have appeared before him, and now, by those who study and rely on his jurisprudence. He was a jurist who cared deeply about the fairness of the criminal justice system and he strived in every decision to arrive at a just result on the law and the facts. Many of Justice Rosenberg’s judgments reflect a concern for the constant struggle of triers of fact to accurately and fairly assess the credibility and reliability of evidence in determining historical events whether it be the testimony of the accused or central Crown witness. This piece explores three decisions from Justice Rosenberg which highlight the different ways in which stereotyping can distort the assessment of credibility and reliability in sexual assault cases: R v. Levert, R v. Rand and, R v. Stark.An important aspect of ensuring accuracy and fairness for Justice Rosenberg was the need to carefully regulate inductive reasoning: the engine that drives judicial reasoning and, ultimately, fact finding. The tools used for inductive reasoning include the decision maker’s or the law’s application of what it sees as common sense, logic and human experience. As an endeavour that explicitly relies on so-called common sense and generalizations about human experience, which shift with time, inductive reasoning can be highly subjective and can easily become a breeding ground for implicit bias, discriminatory stereotyping and unreliable decision-making.
Keywords: David Tanovich